PHIV-RootCell: a supervised image analysis tool for rice root anatomical parameter quantification - Lartaud, Marc; Perin, Christophe; Courtois, Brigitte; Thomas, Emilie; Henry, Sophia; Bettembourg, Mathilde; Divol, Fanchon; Lanau, Nadege; Artus, Florence; Bureau, Charlotte; Verdeil, Jean-Luc; Sarah, Gautier; et al. (Frontiers in Plant Science, 2015)
We developed the PHIV-RootCell software to quantify anatomical traits of rice roots transverse section images. Combined with an efficient root sample processing method for image acquisition, this program permits supervised measurements of areas (those of whole root section, stele, cortex and central metaxylem vessels), number of cell layers and number of cells per cell layer. The PHIV-RootCell toolset runs under ImageJ, an independent operating system that has a license-free status. To demonstrate the usefulness of PHIV-RootCell, we conducted a genetic diversity study and an analysis of salt-stress responses of root anatomical parameters in rice (Oryza sativa L.). Using 16 cultivars, we showed that we could discriminate between some of the varieties even at the 6 day-old stage, and that tropical japonica varieties had larger root sections due to an increase in cell number. We observed, as described previously, that root sections become enlarged under salt stress. However, our results show an increase in cell number in ground tissues (endodermis and cortex) but a decrease in external (peripheral) tissues (sclerenchyma, exodermis and epidermis). Thus, the PHIV-RootCell program is a user-friendly tool that will be helpful for future genetic and physiological studies that investigate root anatomical trait variations.